Anti-inflammatory Activity of Elephantopus scaber and Sauropus androgynus Combination in Pregnant Mice Infected with Escherichia coli - Asfi, Nida; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Rifa’i, Muhaimin; Djati, Muhammad Sasmito (The Journal of Experimental Life Science, 2022)
The current study aimed to investigate the effectiveness of Elephantopus scaber and Sauropus androgynus as anti-inflammatory agents in pregnant mice infected with Escherichia coli. This study used seven treatments group (n=3): K- (healthy pregnant mice), K+ (pregnant mice infected with E. coli), P1 (pregnant mice infected with E. coli + E. scaber 100%), P2 (pregnant mice infected with E. coli + E. scaber 75% and S. androgynus 25%), P3 (pregnant mice infected with E. coli + E. scaber 50% and S. androgynus 50%), P4 (pregnant mice infected with E. coli + E. scaber 25% and S. androgynus 75%), P5 (pregnant mice infected with E. coli + S. androgynus 100%). Flow cytometry analysis was used to analyze cell populations expressing CD4+TNFα+, CD4+IFNγ+ and regulatory T cells (CD4+CD25+CD62L+). All treatment groups significantly (p<0.05) decreased TNFα and IFNγ levels, while the P2 group was more effective in increasing regulatory T cells at the 1st and 2nd trimesters of the pregnancy. This study showed that E. scaber and S. androgynus combination alleviated inflammation by reducing inflammatory cytokines (TNFα and IFNγ) and increasing T-regulatory cells. Therefore, E. scaber and S. androgynus combination could suppress the inflammation during pregnancy and infection. Keywords: Elephantopus scaber, immune system, infection, inflammation, Sauropus androgynous.